Bartolomé de las Casas, OP
1 online resource.
Keywords: Bartolomé de las Casas, O.P.: History, Philosophy, and Theology in the Age of European Expansion marks a critical point in Lascasian scholarship. The result of the collaborative work of seventeen prominent scholars, contributions span the fields of history, Latin American studies, literary criticism, philosophy and theology. The volume offers to specialists and non-specialists alike access to a rich and thoughtful overview of nascent colonial Latin American and early modern Iberian studies in a single text. Contributors: Rolena Adorno; Matthew Restall; David Thomas Orique, O.P.; Rady Roldán-Figueroa; Carlos A. Jáuregui; David Solodkow; Alicia Mayer; Claus Dierksmeier; Daniel R. Brunstetter; Víctor Zorrilla; Luis Fernando Restrepo; David Lantigua; Ramón Darío Valdivia Giménez; Eyda M. Merediz; Laura Dierksmeier; Guillaume Candela, and Armando Lampe.